PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP BIAYA AUDIT - Puteri Permata Septyana Fauzi; Herry Laksito (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to examine the relationships between the ownership structures of the company, namely managerial ownership, foreign ownership, and government ownership as an independent variables to the audit fee agreed by the external auditor. The audit fee illustrates how the client's internal control level was going and the agency conflict that may occur between shareholders and managers. Client leverage, risk, and profitability used as the control variables. This study applies the agency theory as the basis for formulating three hypotheses that guide the results analysis. Using secondary data from 222 non-financial public companies listed in Indonesia Stock Exchange on 2017 that have been selected by purposive sampling technique. The statistical analysis method used is multiple linear regression analysis with Ordinary Least Square model. The results of the analysis shows a significant positive effect between the foreign and government ownership structure on the audit fees. Meanwhile, managerial ownership has negative effect but not significant to the audit fees. Overall, the ownership structures have different influences on the audit fees.